Do Environmental Regulations Attract Foreign Direct Investment Inflows in OIC Countries? - Santika, Ana; Azzaki, Muhammad Adnan; Arifin, Ah. Ali (Jurnal Ekonomi Pembangunan, 2025)
This study investigates the controversial impact of environmental regulations and foreign direct investment (FDI) inflows, specifically in 32 Organization of Islamic Cooperation (OIC) countries from 2005 to 2020. Challenging the widely debated "pollution haven" hypothesis—which posits that lax environmental standards attract FDI—we investigate whether stringent environmental policies deter investment inflows in this underexplored region. Our comprehensive panel data analysis reveals a surprising outcome, strict environmental regulations in OIC nations do not deter FDI. in fact, they may even encourage it. These findings defy conventional wisdom and offer crucial insights for policymakers, suggesting that robust environmental frameworks can enhance a country's attractiveness to foreign investors. This research encourages a fundamental reassessment of how we understand the interplay between environmental stewardship and global investment.